UNCERTAINTY EVALUATION ON THE CALIBRATION OF DC & AC CURRENT GENERATED BY COMBINATION OF AC/DC CURRENT SOURCE AND CURRENT COIL USING SUBSTITUTION METHOD - Lukluk Khairiyati; Hayati Amalia (LIPI Press, Anggota IKAPI, 2020)
Development of measurement method for calibrating current coil continues to be made to maintain measurement traceability for high DC and AC current scope which are generally used for clamp meter calibration services in Laboratory of National Measurement Standard for Electricity and Time (Lab NMS ET). This paper describes the uncertainty evaluation method developed in Lab NMS ET for calibrating high DC and AC current from 50 A up to 990 A generated by a single system consisted of a DC/AC current source and a 50-turn current coil. The uncertainty analysis was carried out based on the calibration principle using the substitution method combined with the principle of multiplication between output current of a DC/AC current source and a 50-turn current coil. It resulted in six source of uncertainty component derived from the current source, the current coil, and a meter. Their sensitivity coefficients were calculated as well to adapt the unit of each uncertainty budget to the final unit in Ampere (A). Using this uncertainty evaluation principle, at the measuring range of 50 A to 990 A, the expanded uncertainties for DC current were spanned from 0.69% to 1%. As for AC current, they were spanned from 0.8% to 1.4%. The major uncertainty contribution comes from the current coil which is representation of uncertainty due to various factors affecting the current coil performance. Validation had been carried out and the normalized error (EN number) values were in the range -0.48 to -0.16 for DC current measurements and in the range of -0.06 to 0.16 for AC current measurements.